Seismic refraction investigation of the shallow bedrock in New Qena City, Eastern Desert, Egypt - Ahmed M. Abdelgowad; Assem E. El-Haddad; Mohamed I. Aglan; Ahmed Hamed (Scientific Reports)
Abstract The seismic refraction technique has demonstrated its efficiency as a cost-effective geophysical approach for bedrock investigation, which is very important for major construction projects. In the southern part of New Qena City, in the Eastern Desert of Egypt, construction of many domestic facilities is planned. Therefore, a prior investigation focusing on bedrock is required to validate the site for construction and other projects. In this study, a site investigation of the southern part of New Qena City is conducted using the seismic refraction method to estimate the depth and thickness of the bedrock and to present the subsurface structural features affecting the area. Ten seismic refraction profiles were measured, and the data were used for tomographic inversion. The results revealed a four-layered subsurface, with the bedrock represented by the mudstone unit of the Pliocene Durri Formation. This layer is located at a shallow depth and exhibits relatively low velocities as well as lateral velocity variations. This is attributed to the clay content of the layer, the high degree of fracturing, and the lateral facies variation. Therefore, the layer could undergo geotechnical problems that could affect future construction projects in the area. Ten subsurface faults were also detected in the velocity sections.